Reflections on 30 Years of Taking Care of Patients with Pelvic Floor Disorders - Hull, Tracy L. (Clinics in Colon and Rectal Surgery, 2025)
Over the past three decades care of patients with pelvic floor disorders has changed dramatically. Fecal incontinence surgery that initially was repair or encircling the anal sphincter now is treated as a first line with sacral nerve stimulation. Rectal prolapse surgery has benefited from minimally invasive approaches and an abdominal approach is considered even in older frail individuals. Medication for constipation has dramatically helped more patients avoid surgery. A multidisciplinary approach with surgeons operating during the same anesthesia on the middle/anterior pelvis and posterior pelvis is common. Evaluation of outcomes and patient-reported outcomes are the norm. We have come a long way toward care of this group of patients, but we still have huge steps to achieve to optimize care as we look toward the next 30 years.
Keywords: fecal incontinence; rectal prolapse; slow-transit constipation; outlet constipation; rectovaginal fistula